Access to the Civil Service in the Democratic Republic of Congo: Reading of Law No. 16/013 of July 15, 2016 on the status of career agents in State public services. - Obed Kongolo Kanowa (Fakultas Hukum Universitas Lampung, 2023)
Access to the public service is a guaranteed right for all Congolese in the Democratic Republic of Congo. This right of access to the public service is framed by legal texts which determine the conditions of recruitment to the public service, the methods of recruitment … in Congolese law, there are several legal texts relating to the statutes of the public service. As a result, this study is particularly structured around law n°16/013 of July 15, 2016 on the status of career agents in the State's public services. Thus, within the framework of this study, removed the prolegomena, we deciphered the question of the access to the public service in Congolese Positive Law, by making a taxonomy of the related conditions and by elaborating on the recruitment as a modality of access to the civil service in accordance with the legal texts in this case. In order to carry out this study, we have recourse from time to time to Comparative Law. These are the main features of this study.